Ensemble Combo Band For The Visually Impaired Person At SLB Negeri 1 Dauh Puri Klod, Denpasar Barat (Universitas Negeri Semarang, 2022)
SLB Negeri 1 Denpasar is one of the knowledge forums for children with special needs, one of them is visually impaired, for them to be able to study, and develop their talents in art, especially music. This research focuses on the process and role provided through the ensemble music combo band for children with visual impairments. This research uses a descriptive qualitative approach with 3 (three) aspects of the discussion that are methods and stages in playing music, the role of ensemble music, and the impact given by combo band ensemble music. Data collection techniques are used observation, interviews, documentation, and literature studies. The theories used in this research are musicology theory and music psychology. The source of this research data was obtained from data in the field in the form of primary data and secondary data from books or other literature studies. The results of the research explained that this had a positive impact. The role of music in each visually impaired individual can help in the development of their character such as a sense of discipline, responsibility, and self-confidence. Meanwhile, through the music ensemble, combo bands can be a medium to create collaboration and social interaction because this activity requires communication, cooperation, emotional and ego control as well as openness in playing music.